Wage-vacancy contracts and coordination frictions - JACQUET, Nicolas L. (Institutional Knowledge at Singapore Management University, 2012)
We consider a directed search model with risk-averse workers and risk-neutral entrepreneurs who can set up firms that post wage-vacancy contracts, i.e., contracts where firms can make payments to more than one applicant, and where the payments can be different for each applicant and be contingent on the number of applicants. We establish that the type of contracts the literature focuses on are not offered if firms can post wage-vacancy contracts. We show that there exists an equilibrium satisfying a Monotonic Expected Utility property which is efficient. Furthermore, we investigate the role of wage-vacancy contracts on welfare and competition.